A trend analysis of the burden of lower extremity peripheral arterial disease in China, 1990 to 2021: based on the Global Burden of Disease Study 2021 - Zhang, Chen; Chen, Mo; Huang, Xintao; Lu, Hao; Wang, Junyu; Liu, Enze; Xiao, Landan; Deng, Huisheng (Frontiers in Public Health, 2025)
The present study provides a thorough trend analysis of the burden of lower extremity peripheral arterial disease (PAD) in China during 1990–2021, based on data from the Global Burden of Disease Study 2021. Lower extremity PAD is an atherosclerotic disease that causes obstruction of blood vessels supplying the legs, presenting as intermittent claudication, rest pain, non - healing wounds, ulcers, or gangrene, and may lead to limb amputation or death due to critical limb ischemia. Our analysis covers prevalence, incidence, mortality, years lived with disability (YLDs), years of life lost (YLLs), and disability - adjusted life years (DALYs). A key finding of this study is from the Age - period - cohort (APC) analysis. It shows that age and period effects are risk factors for the incidence and mortality of PAD, while birth cohort effects have a protective role. Additionally, projections using the Autoregressive Integrated Moving Average (ARIMA) model indicate that the risk of death from PAD will increase for males in the future. Through Joinpoint regression analysis, we delineate the temporal trends. Considering China’s aging population, the growing disease burden from economic progress, and the rapidly changing healthcare landscape, these findings highlight the escalating challenge of PAD. The study’s predictions serve as a warning of the continued rise in PAD incidence and emphasize the urgent need for public health interventions to address the increasing burden.